1994
DOI: 10.1088/0953-8984/6/9/017
|View full text |Cite
|
Sign up to set email alerts
|

Local moments in the paramagnetic phase of dilute CrV alloys

Abstract: The magnetic susceptibility of Cr+0.2 at.% V and Cr+0.4 at.% V alloys (nominal concentrations) is found to show a sharp increase at the Neel temperature with increasing temperature and to obey a Curie-Weiss law in the paramagnetic phase up to 400 K, corresponding to a moment per V atom of about one Bohr magneton. The relation of these results to the behaviour of other physical properties of dilute CrV alloys is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

1994
1994
1998
1998

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 29 publications
(5 reference statements)
4
13
0
Order By: Relevance
“…It turns out in fact that V strongly affects many other physical properties, including (Fawcett, 1992) inelastic neutron scattering, nuclear magnetic relaxation time, the nature of the Néel transition, electrical resistivity in the paramagnetic phase, and the magnetoelastic properties. We shall consider here only the appearance with V doping of a component of the susceptibility χ(T ) in the paramagnetic phase having a temperature dependence that obeys a Curie-Weiss law (Hill et al, 1994). CrMn alloys, on the other hand, have been found to exhibit remarkable spin-glass properties at low temperatures (Galkin et al, 1995(Galkin et al, , 1996b(Galkin et al, , 1997a.…”
Section: Impurity Statesmentioning
confidence: 99%
See 2 more Smart Citations
“…It turns out in fact that V strongly affects many other physical properties, including (Fawcett, 1992) inelastic neutron scattering, nuclear magnetic relaxation time, the nature of the Néel transition, electrical resistivity in the paramagnetic phase, and the magnetoelastic properties. We shall consider here only the appearance with V doping of a component of the susceptibility χ(T ) in the paramagnetic phase having a temperature dependence that obeys a Curie-Weiss law (Hill et al, 1994). CrMn alloys, on the other hand, have been found to exhibit remarkable spin-glass properties at low temperatures (Galkin et al, 1995(Galkin et al, , 1996b(Galkin et al, , 1997a.…”
Section: Impurity Statesmentioning
confidence: 99%
“…Temperature dependence of the magnetic susceptibility χ(T ) of pure Cr and two dilute CrV alloys. The line through the data points above the Néel temperature, T N = 311 K, for Cr is a quadratic fit to χ(T ) (from Hill et al, 1994).…”
Section: Impurity Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…When one introduces these impurities in Cr, the temperature dependence of the magnetic susceptibility shows a Curie-Weiss ͑CW͒ behavior below and above T N . However, for alloys with V, [4][5][6] Si, 7 Rh, 8 Mo and W, 9 this behavior is present only above T N . In particular for dilute CrV alloys, the magnetic susceptibility develops a CW component only above T CW , a temperature previously defined, 5 which is somewhat higher than T N .…”
Section: Introductionmentioning
confidence: 97%
“…It has been suggested that the rapid drop in amplitude scale on the first introduction of vanadium is associated with the decrease in the nuclear spin-lattice relaxation rate and the electrical resistivity, and perhaps also with the recently discovered formation of local moments, in dilute Cr͑V͒ alloys. 19 Remember that the tricritical point also lies between pure chromium and 0.2 at. % V, 12 and so there is scope for subtle effects to occur in this region.…”
Section: Discussionmentioning
confidence: 98%